Intersecting Roles of Authority and Marginalization: International Teaching Assistants and Research University Power Dynamics - Jones, Veronica; Kim, Yughi; Ryu, Wonsun (Journal of International Students, 2020)
The higher education community often views international students through a homogenous lens. To challenge the cultural norms set by the dominant group, researchers need to explore how these norms affect international teaching assistants (ITAs). The following questions guided the current study: (a) How do ITAs construct intersecting identities of teacher and learner that reflect the presence of dominant cultural norms within a predominantly White institution? (b) What strategies do ITAs use to navigate cultural and linguistic power dynamics within a predominantly White institution as they seek to establish authority? We conducted a case study through an intersectionality framework. Findings revealed participants’ marginalization, authority, and strategies to overcome oppression. We offer recommendations about power dynamics that require increased institutional support.